Peranan Aisyiyah Cabang Sebangau di Lahan Gambut Kota Palangka Raya dalam Ketahanan Pangan: The Role of Aisyiyah Sebangau Branch in Peatland of Palangka Raya City on Food Security - Sanawiah, Sanawiah; Rahmaniati, Rita; Marlina, Sari (Anterior Jurnal, 2024)
Aisyiyah is an Islamic women's movement organization formed by Muhammadiyah, this organization since its inception until now, even more, and more various efforts have been made, including in the fields of religion, education, social and economics, which have benefited the Indonesian people in general and Muslims in particular. One of the 'Aisyiyah movements in the social field is the establishment of Posbakum Aisyiyah in collaboration with the Indonesian Ministry of Law and Human Rights, from the Central Leadership of 'Aisyiyah to the regions. The existence of 'Aisyiyah reached the Regional Leader of 'Aisyiyah Central Kalimantan, at the time of the current Covid-19 Pandemic, the role of women has become more increased in domestic roles as well as in fulfilling the economic needs of the family at this time. This study aims to describe the role and form of the role of 'Aisyiyah Kalampangan Branch in Peatlands to Women in increasing family food security. This research was conducted at 'Aisyiyah Kalampangan Branch, Palangka Raya City, Jalan Mahir Mahar Trans Kalimantan Palangka Raya using observation methods (field and participation), interviews (in-depth interviews, taking notes, recording, listening, observing, and capturing using a camera) and literature studies. Data analysis used a simple tabulation to describe the conditions and characteristics of the research site. The processed data is displayed in a table. The targeted finding in this research is the obtaining of a role description by 'Aisyiyah Kalampangan Branch in Peatlands of Palangka Raya City.